GENDER OPPRESSION IN THE MALEFICENT MOVIE BY ROBERT STROMBERG: A FEMINIST PERSPECTIVE - Maulina, Rizky Dwi; Nurhidayat, Nurhidayat (Jurusan Sastra Indonesia, 2024)
Gender oppression remains a pervasive issue in society, frequently depicted in various forms of media, including fairy tale adaptations. Rooted in societal constructions that favor men, this oppression manifests through both explicit and implicit mechanisms, positioning women as subordinate. This research investigates the portrayal of gender oppression in Robert Stromberg's Maleficent (2014) using a feminist literary analysis. Employing liberal feminist theory, the study examines the film to uncover the dynamics of gender oppression. The analysis identifies three primary outcomes: the indicators of gender oppression present in the film, the depiction of this oppression through character, style, and diction, and the contextual reasons behind the film's emphasis on gender oppression, which are linked to the personal experiences of its creators. The findings contribute to a broader understanding of how gender oppression is constructed and represented in contemporary media.